Analisis Kebijakan BPJS Ketenagakerjaan Terhadap Karyawan di Suatu Perusahaan (Kota Batam) - Wulandari, Ayu; Oktavia, Yunisa (Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
The employment BPJS policy towards employees in a company in batam city is an obligation for the owner of the company to perform his obligations in managing the rights for employees who work in his company, such as in terms of managing BPJS, namely BPJS Employment and BPJS Health. This is done because, to guarantee employees against the existence of work accident insurance programs (JKK), old age insurance (JHT), pension insurance, death insurance (JKM) and health insurance. That way, company owners and the government must work together to give rights to company employees. The purpose of this analysis can be carried out because it is to be able to provide a bridge for the welfare of workers based on a program against employment social security, which will always be committed to protecting and welfare for a working employee and his family. This analysis is carried out on the basis of retrospective policy analysis methods and descriptive methods. Which, systematically, factually and accurately about the facts, and obtains information in real or based on news, magazines, and based on journals. By conducting this analysis, not only does it produce a goal, but there are also suggestions in this analysis, namely to improve employees in their work, and to be able to give confidence to their employees in ensuring the safety of their distance in the company, especially in the city of Batam. which is known as the city of industry.